Meningkatkan Kesediaan Merawat Orang Dengan HIV/AIDS (ODHA) Pada Perawat Puskesmas Dengan Menggunakan Metode A Brief Intervention: Improving the Willingness to Care for People with HIV/AIDS (PLWHA) Among Health Center Nurses Using the Brief Intervention Method - Ari Athiutama; Arina Widya Murni; Tasman (NERS Jurnal Keperawatan, 2020)
HIV/AIDS is a problem for health workers, especially nurses, which results in negative things such as the stigma of discrimination in health services so the treatment of PLWHA is being not optimal. The purpose of this study is to determine the effect of a brief intervention on the public health center nurses on the willingness to treat PLWHA. The design of this study is the Quasy Experiment Pre-Post Test With Control Group the sample is 48 nurses consisting of 24 nurses in the intervention group and 24 nurses in the control group selected by using total sampling techniques. Data were collected by using a nursing willingness questionnaire (NWQ) that was translated into Indonesian languages and analyzed using the paired sample t test and independent samples t test. The results showed there were differences in the willingness to care on pre and post-test intervention group (p value = 0.001) and there is difference in the willingness to care the intervention group and the control group (p value = 0.027). The conclusion of a brief intervention method is effective in increasing willingness to treat PLWHA on public health center nurses. A brief intervention method as an innovation method that can be used in public health center to share information, especially regarding willingness to treat PLWHA.